Modelling of phosphorus accumulation in an aeroponic coriander crop - Santamaría, Alejandro Rincón; Candelo-Becerra, John E.; Velasco, Fredy E. Hoyos (International Journal of Agricultural and Biological Engineering, 2022)
A model was developed for phosphorus (P) concentration over time in a closed aeroponic coriander culture. In addition, the setting and starting up of the soilless culture is described, and the measurements of electrical conductivity (EC), pH and concentration of major ions in the mixing tank are provided. By using mass balance principles, the dynamics of the nutrient concentration in the mixing tank and in the drainage solution are stated. Two series of continuous stirred tank reactors are considered for the flow structure, using a power law relationship to represent the rate of nutrient removal, considering water volume changes. Phosphorus concentration measurements were used for model fitting, and the resulting simulation is in good agreement with data. Keywords: aeroponic culture, hydroponics, soilless culture, nutrient modelling, Coriander sativum DOI: 10.25165/j.ijabe.20221506.6760 Citation: Rincón A, Candelo-Becerra J E, Hoyos F E. Modelling of phosphorus accumulation in an aeroponic coriander crop. Int J Agric & Biol Eng, 2022; 15(6): 73–79.